Homo Mimeticus II: re-turns to Mimesis - Lawtoo, Nidesh; García-Granero, Marina (Leuven University Press, 2024)
Second volume in the Homo Mimeticus mini-series, which advances the emerging transdisciplinary field of mimetic studies After the linguistic and the affective turns, the new materialist and the performative turns, the cognitive and the posthuman turns, it is now time to re-turn to the ancient, yet also modern and still contemporary realization that humans are mimetic creatures. In this second installment of the Homo Mimeticus series, international scholars working in philosophy, literary theory, classics, cultural studies, sociology, political theory, and the neurosciences engage creatively with Nidesh Lawtoo's Homo Mimeticus: A New Theory of Imitation to further the transdisciplinary field of mimetic studies. Agonistic critical engagements with precursors like Plato, Aristotle, Nietzsche, Bataille, Irigaray and Girard, involving contributions by leading international thinkers such as Mikkel Borch-Jacobsen, William E. Connolly, Henry Staten and Vittorio Gallese among many others, reveal the urgency to rethink mimesis beyond realism. From imitation to identification, mimicry to affective contagion, techne to simulation, mirror neurons to biomimicry, homo mimeticus casts a shadow—but also a light—on the present and future, from social media to the Anthropocene